Availability in ECMO Reduces the Failure to Rescue in Patients With Pulmonary Embolism After Major Surgery: A Nationwide Analysis of 2.4 Million Cases - Johannes Diers, MD; Nikolas Baumann, MD; Philip Baum, MD; Konstantin L. Uttinger, MD; Johanna C. Wagner, MD; Peter Kranke, MD; Patrick Meybohm, MD; Christoph-Thomas Germer, MD; Armin Wiegering, MD (Annals of Surgery Open)
Objective:. Postoperative pulmonary embolism (PE) is a rare but potentially life-threatening complication, which can be treated with extracorporeal membrane oxygenation (ECMO) therapy, a novel therapy option for acute cardiorespiratory failure. We postulate that hospitals with ECMO availability have more experienced staff, technical capabilities, and expertise in treating cardiorespiratory failure. Design:. A retrospective analysis of surgical procedures in Germany between 2012 and 2019 was performed using hospital billing data. High-risk surgical procedures for postoperative PE were analyzed according to the availability of and expertise in ECMO therapy and its effect on outcome, regardless of whether ECMO was used in patients with PE. Methods:. Descriptive, univariate, and multivariate analyses were applied to identify possible associations and correct for confounding factors (complications, complication management, and mortality). Results:. A total of 13,976,606 surgical procedures were analyzed, of which 2,407,805 were defined as high-risk surgeries. The overall failure to rescue (FtR) rate was 24.4% and increased significantly with patient age, as well as type of surgery. The availability of and experience in ECMO therapy (defined as at least 20 ECMO applications per year; ECMO centers) are associated with a significantly reduced FtR in patients with PE after high-risk surgical procedures. In a multivariate analysis, the odds ratio (OR) for FtR after postoperative PE was significantly lower in ECMO centers (OR, 0.75 [0.70–0.81], P < 0.001). Conclusions:. The availability of and expertise in ECMO therapy lead to a significantly reduced FtR rate of postoperative PE. This improved outcome is independent of the use of ECMO in these patients.